Associations of sarcopenia status and its components with the risk of developing functional disability in older Chinese adults: evidence from the China health and retirement longitudinal study - Zhang Hao; Lin Haoxiang; Lin Shujun (BMC Public Health)
Abstract Objectives In the aging population, sarcopenia has become a major concern due to its association with increased risks of disability, including impairments in both activities of daily living (ADL) and instrumental activities of daily living (IADL). This relationship, however, has been rarely studied within the Chinese population. This study was conducted to assess the relationships of sarcopenia status and its components with the risk of developing ADL/IADL disability among Chinese community-dwelling elderly people. Methods In this study, we used data from the China Health and Retirement Longitudinal Study. The ADL and IADL scales were used to assess an individual’s functional disability. Logistic regression models were used to assess the association between sarcopenia status and its components and the risk of developing ADL/IADL disability in the overall population. Sex-specific receiver operating characteristic (ROC) curves was used to evaluate the value of sarcopenia component indicators for predicting ADL/IADL disability. Results A total of 4,893 participants were included in the study, comprising 2,220 males and 2,673 females, with ages ranging from 60 to 102 years. There were greater IADL disability risks in the possible sarcopenia group (OR = 1.87, 95% CI: 1.48–2.37), sarcopenia group (OR = 1.85, 95% CI: 1.24–2.76) and severe sarcopenia group (OR = 2.54, 95% CI: 1.63–3.94). The results were similar (possible sarcopenia: OR = 2.16, 95% CI: 1.44–3.22; severe sarcopenia: OR = 4.99, 95% CI: 2.52–9.87)) for ADL disability, except for the sarcopenia group (OR = 2.00, 95% CI: 0.97–4.12). We found that handgrip strength (HS) (OR = 0.95, 95% CI: 0.92–0.97) and gait speed (GS) (OR = 0.33, 95% CI: 0.12–0.86) were negatively associated with the risk of developing ADL disability and that the repeated chair stand (RCS) test results (OR = 1.09, 95% CI: 1.05–1.12) were positively associated with the risk of developing ADL disability. Similar results were found for the associations between several sarcopenia component indicators and the risk of developing IADL disability. The area under the curve (AUC) of HS was 0.702, which could better recognize ADL disability and showed good discriminant validity in males. Conclusion The prevalence of sarcopenia is high among the elderly Chinese population. Additionally, HS showed good discriminant validity for discriminating ADL disability in males. Further prospective studies are needed to clarify the relationship between sarcopenia status and the risk of developing functional disability and to determine whether indicators of the separate sarcopenia components can be used for early warning, screening and identifying functional disability.